Cryopreservation of primary trypsinized fibroblast cells of chicken embryos using various cryoprotectants - S. P. Lazareva; B. L. Manin; N. S. Mudrak; D. B. Andreychuk (Ветеринария сегодня)
Cryopreservation is the optimal way to store cells at ultra-low temperatures. Cryoprotectants are added to cell culture suspension to reduce cell death due to exposure to low temperatures. Cryoprotective media contain combinations of various cryoprotectants. Ethylene glycol, glycerin, dimethyl sulfoxide, sucrose, dextran, propylene  glycol, albumin, polyvinylpyrrolidone and blood serum can be used as cryoprotectants. For cryopreservation it is necessary  to select a cryoprotectant that ensures the highest survival of cells after storage and thawing. The paper presents  the results of experiments  on comparing the effectiveness of dimethyl sulfoxide, ethylene  glycol and glycerin in cryopreservation  of primary trypsinized chicken embryo fibroblasts. As a result of cell suspension  equillibration  (incubation  at room temperature) with serum and the specified cryoprotectants at different concentrations, the suspension variants containing different cryoprotectant and serum ratios were selected for freezing. Previously, it was found that after 12 months of observation, when using dimethyl sulfoxide as a cryoprotectant,  the largest number of surviving cells (46%) was observed in a suspension  containing  20% fetal serum and 10% dimethyl sulfoxide. The amount of surviving  cells if 10% fetal serum  and 5% ethylene  glycol were included in the cryoprotective mixture was slightly lower and amounted  to 36% after 12 months of observation. Glycerin is shown  to have weak protective properties as regards chicken embryo fibroblast cells. After 8 months of storage, the amount of surviving cells in a suspension containing 10% serum and 5% glycerin was 22%, no live cells were found in this mixture if stored longer. The proliferative properties of cells and their sensitivity to viruses remained within the 12 months  of the experiment.